Analysis of Maxim Violations on Japanese Comic Strip â€œKariage Kunâ€ Vol 49 and its Indonesian Translation - Andi Sutrisno (Program Magister Linguistik Universitas Udayana, 2023)
Humor could be created by violation of maxim of the cooperative principle as proposed by Grice. In Kariage Kun, a well-known Japanese humor comic, it is challenging to analyze what maxim violation is explored to create humor, as it represents a co-interplay between a series of images and text. This study aimed to analyze the pattern of maxim violation in source text from Kariage Kun vol 49 (from word level to sentence level) and to compare whether the pattern of maxim violation is similar or shifting in the Indonesian version. The result of this study shows that the author of the comic explored the violation of maxims to create humor. The violation took place on a single or combination of the maxim of quantity, the maxim of quality, the maxim of relevance, and the maxim of manner. Compared to the target text, there are not many (less than ten percent) shifting of the pattern of maxim violation in the target text. The shifting mostly occurred when the violation dealt with the ambiguity of typical cultural load in the source text, preservation of acceptability and readability for target readers in terms of translation technique, and limited space of speech balloon.